Inovasi Nelayan pada Ekowisata Kampoeng Kepiting, Tuban, Bali - Putu Wira Parama Suta; Ni Putu Lilik Widyayanthi; Anak Agung Ayu Ratih Kesumadewi; Pande Putu Juniarta (Yayasan Literasi Sains Indonesia, 2025)
Fishermen community in the Tuban area is well aware of the ongoing tourism activities and criticizes these activities for providing limited benefits to them. By utilizing the mangrove ecosystem, the local fishermen in Tuban are attempting to develop ecotourism based on education and mangrove conservation. This study aims to explore the innovations made by fishermen at Kampoeng Kepiting Ecotourism, Tuban, Bali. This research is important because the role of the fishing community in innovation at Kampoeng Kepiting Ecotourism can determine the sustainability of the mangrove ecotourism in Tuban Village. The discovery and development of innovations that utilize the mangrove ecosystem as a foundation make Kampoeng Kepiting ecotourism offer unique tourist attractions not found elsewhere. The research methodology used is qualitative, employing qualitative observation, interviews, and document analysis to examine field issues, complemented by a flowchart illustrating the relationship between participation and innovation in Kampoeng Kepiting Ecotourism. The results depict a mutually supportive relationship between the Wanasari fishermen group, ecotourism innovations, and Bali’s ecotourism programs in achieving the sustainability of Kampoeng Kepiting Ecotourism. The fishermen group, as the main actors, plays a role in innovation and program implementation, which contributes to the overall sustainability of the ecotourism. The role of the fishing community in effectively running ecotourism programs and the innovations at Kampoeng Kepiting Ecotourism are reflected in the creation and development of tourist attractions as well as the relationship between the fishermen’s roles and innovation.